Three essays in international trade theory and policy - Sargsyan, Ruben (Kansas State University, 2008)
Concerns over the possible loss of government revenue resulting from tariff reductions under trade liberalization have triggered many developing countries to opt for a strategy of raising destination-based consumption taxes on tradable goods. The first essay analyzes the welfare effects of a coordinated tariff reduction and domestic tax reform when the objective of a reforming country is to keep its government revenue unchanged. Assuming imperfect competition in an import-competing industry, we find that revenue-neutral reform involving tariff reduction and an increase in domestic tax rate may reduce domestic welfare under plausible assumptions. It also discusses the scenario in which the reforming country's objective is to keep domestic profit (or production) unchanged. We further identify the conditions under which a profit-neutral tariff and tax reform may be welfare-improving or welfare-deteriorating. The second essay uses a reciprocal-dumping model to examine the welfare effects of the Byrd Amendment (i.e., the Continued Dumping and Subsidy Offset Act, or CDSOA). It analyzes the differences in optimal tariffs set by the home and foreign governments when the home (i.e., the U.S.) government redistributes anti-dumping duties to its domestic firm under the new trade law, as compared to the traditional antidumping policy under which these duties are government revenues. We derive conditions under which the CDSOA may raise or lower the price of an import-competing good in the U.S. market. The results show that the CDSOA is an instrument of protectionism and strictly improves the home country welfare when markets are less competitive than in Cournot equilibrium. We find that under the same market characteristics, the new trade law strictly reduces foreign country welfare. The CDSOA's welfare effect is shown to be ambiguous, however, when markets are more competitive than Cournot. The third essay modifies the model presented in Essay 2 to allow for the scenario in which the foreign country strategically responds to the home country's CDSOA law by adopting similar trade law. The results show that the foreign country is able to enhance its national welfare when the import-competing markets are less competitive than in the Cournot equilibrium. We also discuss whether it is welfare-improving for the U.S. to voluntarily repeal the Byrd Amendment and restore the traditional antidumping policy, considering that, otherwise, its trading partner may also adopt the CDSOA law. We find that it is still in the best interest to the U.S. not to revoke the Byrd Amendment when markets are less competitive than Cournot. When markets are more competitive than Cournot, however, repealing the Amendment may turn out to be socially welfare-improving.
Keywords: The Byrd Amendment; Optimal tariff; Tariff and tax reforms; Economics, General (0501); Economics, Theory (0511)